Study the impact of marketing mix on Customer satisfaction case study of condor brand. - Attallah, Lahcen (Finance and Business Economies Review, 2019)
The objective of this research is to study the impact of the marketing mix on the Customer satisfaction for the condor brand, In order to determine this effect, we conducted an applied study in which a number of customers of the condor brand were distributed to about 120 customers ،The structural equation modeling(SEM) and multiple regression model was used to analyze the study data to illustrate the direction and strength of the relationship between the marketing mix and the Customer satisfaction. We have concluded from this study that there is a positive impact of the marketing mix on the Customer satisfaction for the condor brand. There is also a positive effect of the product, price, promotion, distribution on the Customer satisfaction for the condor brand.